2017
DOI: 10.18632/oncotarget.17012
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microRNA-205-5p in human mesenchymal stem cells improves their therapeutic potential in treating diabetic foot disease

Abstract: Diabetes is a prevalent disease endangering human health, while diabetic foot disease (DF) is one of the most severe complications of diabetes. Mesenchymal stem cells (MSCs) have been used in DF treatment, taking advantage of the differentiation potential of MSCs into endothelial cells and their production and secretion of trophic factors like vascular endothelial growth factor (VEGF). Molecular modification of MSCs to improve their therapeutic effects has been recently applied in treating other diseases, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…The recent evidence showed that the dysregulated miR‐205 expression occurred in the early stage of DM . Regulating miR‐205 in mesenchymal stem cells might improve the therapeutic effects on diabetic foot disease, one severe complication of DM . This might be the first study indicating the regulatory effect of BAI on miR‐205.…”
Section: Discussionmentioning
confidence: 78%
“…The recent evidence showed that the dysregulated miR‐205 expression occurred in the early stage of DM . Regulating miR‐205 in mesenchymal stem cells might improve the therapeutic effects on diabetic foot disease, one severe complication of DM . This might be the first study indicating the regulatory effect of BAI on miR‐205.…”
Section: Discussionmentioning
confidence: 78%
“…These injuries are associated with impaired endothelial cell tube formation (24). Several studies have reported that the dysregulation of miRNA in diabetic endothelial cells influences their functions (25,26). Therefore, targeting and regulating miRNA in an advanced pathway is a strategy for overcoming HG-induced endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…In another study the suppression of miRNA‐205‐5P, as a VEGF antagonizing miRNA in MSCs, was performed. Consequently, it enhanced VEGF and the pro‐angiogenic effects of MSCs which improved MSC therapeutic efficacy in the treatment of diabetic foot disease …”
Section: Methods To Enhance the Efficacy Of Msc‐based Wound Therapymentioning
confidence: 99%
“…Consequently, it enhanced VEGF and the pro-angiogenic effects of MSCs which improved MSC therapeutic efficacy in the treatment of diabetic foot disease. 76…”
Section: Genetic Modificationsmentioning
confidence: 99%